2013
DOI: 10.1098/rspb.2012.2784
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic and mechanical costs of step time asymmetry in walking

Abstract: Animals use both pendular and elastic mechanisms to minimize energy expenditure during terrestrial locomotion. Elastic gaits can be either bilaterally symmetric (e.g. run and trot) or asymmetric (e.g. skip, canter and gallop), yet only symmetric pendular gaits (e.g. walk) are observed in nature. Does minimizing metabolic and mechanical power constrain pendular gaits to temporal symmetry? We measured rates of metabolic energy expenditure and calculated mechanical power production while healthy humans walked sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 38 publications
4
102
0
2
Order By: Relevance
“…In this condition, step length of the affected leg further increased with swing assistance, rather than returning to the baseline level during the late adaptation period, indicating that neural systems did not generate additional torques to counteract the deviation in step length of the affected leg induced by swing assistance. Instead, subjects walked with swing assistance and demonstrated a greater level of step length symmetry, which may be driven by the improved energy efficiency of symmetric gait (Ellis et al, 2013). Following the release of swing assistance, step length of the affected leg did not fall below the baseline, i.e., no aftereffect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In this condition, step length of the affected leg further increased with swing assistance, rather than returning to the baseline level during the late adaptation period, indicating that neural systems did not generate additional torques to counteract the deviation in step length of the affected leg induced by swing assistance. Instead, subjects walked with swing assistance and demonstrated a greater level of step length symmetry, which may be driven by the improved energy efficiency of symmetric gait (Ellis et al, 2013). Following the release of swing assistance, step length of the affected leg did not fall below the baseline, i.e., no aftereffect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was demonstrated that the magnitude of step length asymmetry observed during walking on a split-belt treadmill was positively correlated with the metabolic cost 22 . Another study showed that asymmetries in step timing can lead to increases in the mechanical and metabolic cost of walking, potentially as a result of increased power absorption and generation during the double support and single support phases of the gait cycle respectively 23 . However, although these studies provided evidence that asymmetric walking patterns are energetically costly in able-bodied individuals, our understanding of the degree to which asymmetry influences metabolic cost in stroke survivors remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their studies, the performance of lower limbs in healthy people during walking at normal speed is naturally asymmetric, resulting from different functions performed by the lower limbs (Table 1). In these conditions, given that gait symmetry is the ideal state of walking for healthy people [7], the created asymmetry between the lower limbs depends on the conditions. Symmetry seems to be desirable because it facilitates control strategies.…”
Section: Gait Symmetry or Asymmetrymentioning
confidence: 99%
“…As a result, achieving symmetry or reducing the gait asymmetry in people with any disorder before and after rehabilitation has been used as a method for assessing the effectiveness of the therapeutic model [2 -6]. Ellis et al [7] reported that increased gait asymmetry would increase metabolic and mechanical costs, suggesting the gait symmetry as the best prescription for healthy people. Thus, achieving full gait symmetry in most cases is an important target for physiotherapy in people with various diseases and functional anomalies [5,8], although many other papers have not supported this claim [9,10].…”
Section: Introductionmentioning
confidence: 99%